Laser Navigation Combined With XperCT Technology Assisted Puncture of Brainstem Hemorrhage - Wang, Qingbo; Guo, Wei; Zhang, Tao; Wang, Shuangquan; Li, Chenglong; Yuan, Zhengbo; Wei, Qi; Geng, Xin; Li, Zefu (Frontiers in Neurology, 2022)
Abstract Background: Brainstem hemorrhage has a rapid onset with high mortality and disability rates. In recent years, an increasing number of studies have reported on the surgical treatment of brainstem hemorrhage. The introduction of stereotaxic instruments and navigation systems has improved the accuracy of surgical treatment; however, the popularity of these devices in primary hospitals is not high. Herein, we introduced laser navigation combined with XperCT technology to assist in the puncture and drainage of brainstem hemorrhage, aiming to improve surgical accuracy and facilitate the drainage of brainstem hemorrhage in primary hospitals. Material and Methods: A total of 5 patients, 4 men and 1 woman, aged 34–70 years, who underwent hematoma puncture drainage with the assistance of laser navigation combined with XperCT technology at Binzhou Medical University Hospital, China, between June 2020 and Aug 2021 were included in the study. The brainstem hemorrhages had volumes of 7–18 mL. Statistical analyses of the postoperative puncture deviation distance (distance between the actual puncture end and simulated puncture end) and postoperative improvement were also performed. Results: The operations were successfully completed in all 5 patients. The puncture deviation distance was < 6 mm in all 5 patients and < 2 mm in 2 patients. The postoperative hematoma clearance rate was about 70%–90%. Among 4 patients with respiratory failure, 3 had improved breathing and resumed spontaneous breathing. Among 3 patients with high fever, 1 showed a substantial decrease in body temperature. There were no cases of postoperative infection. Of the 5 patients, 2 recovered consciousnesses, 1 died, and 2 voluntarily gave up further treatment and were discharged. Conclusions: Laser navigation combined with XperCT technology could improve the accuracy of surgical puncture. The technique might be convenient for widespread clinical application because of its low trauma, high precision, short operation time, and low operation cost.